1993
DOI: 10.1007/bf01658700
|View full text |Cite
|
Sign up to set email alerts
|

Current concept of the treatment of biliary atresia

Abstract: Hepatic portoenterostomy (Kasai operation) for the patient with biliary atresia (BA) can restore the bile flow in approximately 80% of children operated on before 60 days of life [1]. However, in terms of long-term survival, according to a recent nationwide survey among the major pediatric centers in Japan, only 325 of 2013 patients had more than 10 years' survival, and only 157 patients (7.8%) remained jaundice-free with normal liver function [2]. About 20% of BA cases without jaundice are generally able to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…Miyano and colleagues [22] showed that although about 70% of their patients had evidence of bile secretion immediately after surgery, only 32% maintained bile secretion after 5 years. However, children successfully treated with adjuvant steroid in Dillon's study [3] seem to maintain their bile flow for 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Miyano and colleagues [22] showed that although about 70% of their patients had evidence of bile secretion immediately after surgery, only 32% maintained bile secretion after 5 years. However, children successfully treated with adjuvant steroid in Dillon's study [3] seem to maintain their bile flow for 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In untreated infants the mean expected survival is about 11 months [8]. The Kasai portoenterostomy, introduced in 1959, can restore bile flow in approximately 62% to 80% of infants operated on before 60 days of life [4,6]. The long-term prognosis for 30% to 50% of those undergoing the procedure is good [9].…”
Section: Discussionmentioning
confidence: 99%
“…Without correction of bile fl ow obstruction within 2-3 months of life, irreversible hepatic damage and complete obliteration of the extrahepatic biliary tree will result. This process could be progressive even after surgical correction of the obstruction [ 114 ]. The neonatal hepatitis syndrome includes various kinds of diseases such as idiopathic neonatal hepatitis, infectious hepatitis, and hepatitis from metabolic or genetic causes.…”
Section: Neonatal Hyperbilirubinemiamentioning
confidence: 99%